134k views
15 votes
3x-2y=1x+4y=33 elimination process ​

User ShooShoSha
by
5.9k points

1 Answer

6 votes

Answer:

x = 5 ; y = 7

Explanation:

3x - 2y = 1 --------------------(I)

x + 4y = 33 ------------(II)

Multiply equation (II) by (-3) and then add. So, x will be eliminated and we can find the value of y

(I) 3x - 2y = 1

(II)*(-3) -3x -12y = -99 {Now add}

- 14y = -98

y = -98/14

y = 7

Plugin y = 7 in equation (I)

3x - 2*7 = 1

3x - 14 = 1

3x = 1 + 14

3x = 15

x = 15/3

x = 5

User Svohara
by
5.8k points